Manchester motorway box: post-survey research of induced traffic effects. - (:unkn) unknown (Routledge, 2012)
In the 1990s, the usual assumption for an appraisal of road schemes in the UK was that total volumes of traffic were not affected by the capacity provided by the schemes. This assumption was questioned by the influential SACTRA committee in 1994, which also recommended that Before and After studies be undertaken to quantify the scale of traffic that would be induced by the provision of road capacity. An opportunity to investigate this issue arose with the completion of the M60 Manchester Motorway Box, one of the last major links in the UK's national road network, and a large program of Before and After data collection was undertaken. The paper describes the analysis that was made of the Before and After data, to which household interview records were added to form a large database linked to modeled level-of-service data and land-use data. This combined dataset has been used to estimate disaggregate models that represent frequency, mode, destination and time-of-day choice decisions within a hierarchical structure. Time-of-day choice has been represented by distinguishing four time periods that cover a day, and modeling the choice between those four time periods. The use of a hierarchical structure allows the scale of the different behavioral effects to be measured in a parametric form and also allows the construction of a detailed (market segmented) travel demand model. A further aim of the analysis was to distinguish the induced traffic effects from any other changes that may have occurred. Analysis of the level-of-service data showed that the conventional assignment procedures used were not able to reproduce the observed changes in journey times between the Before and After situations. Models including mode, destination and time-of-day choices were estimated separately, using observed journey times where available, for intercept surveys (correcting for the trip length bias in that data), for household interview data and then for combined data. The values of time and elasticities implied by the models were found to be reasonable. Application of the models took into account the relevant changes in the population in the period between the Before and After observations. The models indicated that the M60 Scheme is likely to have induced traffic at the level of a 15 17% increase across the most relevant screenline counts, of which the majority were due to destination switching and less to mode shift. Time-of-day effects were found to be negligible, although in the M60 situation, journey time changes across time periods were broadly similar.
Keywords: Verkehr; Verkehrsplanung; Verkehrsweg; Autobahn; Projektbeschreibung; Modellversuch